Dynamics of nuclear fusion reactions within the relativistic effective interaction - Rana, Shilpa (My University, 2024)
The thesis aims to explore the heavy ion fusion mechanism in view of nuclear structure effects in the low-energy domain. The interaction potential, encompassing Coulomb, nuclear, and centrifugal potentials, forms the foundation for comprehending the dynamics of nuclear reactions. Due to the ambiguity surrounding the exact nature of the strong nuclear force, numerous theoretical models have been devised to describe the attractive nuclear potential formed between colliding projectile and target nuclei. The structural properties of these interacting nuclei play an essential role in understanding the nuclear reaction mechanisms. The relativistic mean-field (RMF) formalism is one of well-known approaches adopted to scrutinize various structure properties of finite nuclei. Additionally, the RMF formalism is also well-adopted to understand various properties of infinite nuclear matter. In this research work, the RMF formalism is applied to study heavy ion nuclear fusion. The relativistic effective nucleon-nucleon (NN) interaction named R3Y NN potential and nuclear densities obtained from RMF formalism are used to calculate the microscopic nuclear potential within the double folding approach. The in-medium effects are also incorporated in the description of the relativistic R3Y NN interactions through density-dependent nucleon-meson couplings within the framework of the relativistic Hartree-Bogoliubov (RHB) approach. First, a systematic study is carried out to assess the application of R3Y and density-dependent R3Y (DDR3Y) NN interactions along with RMF and RHB densities to study the fusion barrier characteristics of various heavy ion reactions. Next, the nuclear potential derived from the RMF approach is used to provide a theoretical prediction for the feasible target-projectile combinations for the synthesis of yet-to-be-discovered superheavy nuclei (SHN) with Z = 120. Moreover, the nuclear shape and orientation degrees of freedom are also included in the computation of nuclear interaction potential and fusion cross-section within the RMF formalism. Furthermore, the reliability of various fusion barrier transmission coefficients, supplemented with the relativistic R3Y effective interaction, is assessed to investigate the fusion dynamics of reactions of astrophysical significance at stellar energies.
PhD Thesis of Ms Shilpa Rana
Keywords: Nuclear Fusion; Heavy Ion Reactions; Mean field approach; Double Folding